Structural, electronic and optical properties of Ag-based oxides XAgO (X= Li and Na): An ab initio study - MOUSSA, Hizia (My University, 2021)
Ab initio total energy calculations were performed to study in details the structural, electronic and optical properties of Ag-based ternary oxides BAgO (A B= Li and Na). Optimized atomic coordinates and lattice constants agree well with the existing experimental and theoretical data. Band structure, total and site-projected l-decomposed densities of states, charge transfers and charge density distribution maps were obtained; analyzed and compared with the available theoretical data. Complex dielectric function, refractive index, extinction coefficient, reflectivity and loss function spectra were calculated with an incident radiation polarized parallel to both [100] and [001] crystalline directions
Keywords: Structural, electronic and optical properties of Ag-based oxides XAgO (X= Li and Na): An ab initio study